Active and passive cation transport and L antigen hertogeneity in low potassium sheep red cells - Lauf, PK (The Rockefeller University Press, 1977)
Several lines of experimental evidence are presented suggesting that the L antigens in low potassium (LK) sheep red cells are associated with separate Na(+)K(+) pump flux is distinct from the action of anti-L(l) on K(+) leak flux, implying that K(+) leak transport sites may not be converted into active pumps by the L antiserum. Treatment of LK red cells with trypsin completely abolished both the stimulation of K(+) pump flux and the enhancement of the rate of ouabain binding brought about by anti- L. That this effect is due to a total destruction of the L(p) determinant associated with the LK pump was evident from the complete failure of anti-L(p) to bind to trypsinized LK red cells. The L(p) antigen can be effectively protected against the trypsin attack by prior incubation with anti-L, indicating that the sites for antibody binding and trypsin action may be closely adjacent at the structural level. Trypsin treatment, however, did not interfere with anti-L(l) reducing ouabain insensitive K(+) leak influx, nor did it prevent binding of anti-L(ly), the hemolytically active L antibody which is probably identical with anti-L(l). The functional independence of the L(p) and L(l) sites was documented by the observation that anti-L(l) still reduced K(+) leak influx in LK cells with experimentally induced high potassium concentrations, at which K(+) pump flux is fully suppressed, whether or not anti-L(p) was binding to the L(p) antigen associated with the LK pump.